Increasing the Operational Lifetime of a Printed Enzymatic Power Source using Superabsorbent Polymers as the Anode Support. Issue 11 (11th September 2015) - Tuurala, Saara; Kallio, Tanja; Smolander, Maria; Bergelin, Mikael
Abstract: Superabsorbent polymers (SAPs) were added as a dry powder to the anode side of a printed enzymatic power source. SAPs partially eliminated delamination of the cathode electrode from the current collector and decreased the ohmic losses in the cells. SAPs also retained moisture inside the cells and increased water diffusion through the membrane from the anode side to the cathode side. Moreover, the degradation process of the operational cells was slower due to using the SAPs. Consequently, the operational lifetime of the cells was increased; the electric charge and energy output of the cells doubled in the presence of the SAPs at the anode. Abstract : Superabsorbing results: Superabsorbent polymers (SAPs) are added as a dry powder to the anode side of a printed enzymatic power source, and they increase the adhesion between the printed layers and retained moisture inside the cells. In addition, the degradation process of operational cells is slower due to the use of SAPs. Consequently, operational lifetime of the cells is increased; the electric charge and energy output of the cells doubled in the presence of the SAPs on the anode.